2019
DOI: 10.33836/interacao.v20i1.191
|View full text |Cite
|
Sign up to set email alerts
|

TECHNOPHOBIA AS A CULTURAL AND PSYCHOLOGICAL PHENOMENON: Theoretical Analysis

Abstract: Today we can talk about a sufficient formation of both negative and positive attitudes towards the introduction of new technologies. This is the technophobia that continued to be fueled by such objective factors as job slashing caused by events and new inventions. Technophobia includes cognitive, emotional and behavioral components. Along with individual factors (self-efficacy, open-mindedness, anxiety level, user’s experience, emotional state, etc.), the formation of technophobia is influenced by interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The distrust of technology (algorithms), which might influence connections, partially came from the nature of people's familiarity with technology. Previous research suggested that a lack of accurate information (unknown) and transparency could create a sense of fear around technology (Graham, 2020; Li & Huang, 2020; Nestik et al, 2018; Thielsch et al, 2018). Thus, it is important that users can trust mental health apps and that the public is provided with reliable and accurate information regarding mental health apps.…”
Section: Discussionmentioning
confidence: 99%
“…The distrust of technology (algorithms), which might influence connections, partially came from the nature of people's familiarity with technology. Previous research suggested that a lack of accurate information (unknown) and transparency could create a sense of fear around technology (Graham, 2020; Li & Huang, 2020; Nestik et al, 2018; Thielsch et al, 2018). Thus, it is important that users can trust mental health apps and that the public is provided with reliable and accurate information regarding mental health apps.…”
Section: Discussionmentioning
confidence: 99%
“…H4: Assurance influnces consumer attitude towards acquiring e-consultation Barriers to Users Technophobia refers to any type of fear, resistance, or intimidation toward new technology usage caused by lack of self-efficacy, anxiety level, user experience, and so on. This phenomenon is emerging as a challenge in the business model of new technology adaptation (Nestik et al, 2019). Another barrier is a client who does not own any digital device can not acquire e-consultation service (Jeong et al, 2021).…”
Section: Literature Review Service Costmentioning
confidence: 99%
“…In addition, consumers are psychologically concerned about trust (supply chain and brand), membership and privacy, regulations, and social obligations (Gupta et al., 2015). The usage barrier regarding the app and software or skills to handle the advanced technologies might result in technophobia (Nestik et al., 2018). This, in turn, implies that the social and individual awareness or education prior to the introduction of new technology must be achieved; otherwise, the lack of awareness results in neophobia, thereby causing unacceptability of the innovations (Barska & Wyrwa, 2016).…”
Section: Opportunities and Challenges In Packaging 40mentioning
confidence: 99%